2008
DOI: 10.5650/jos.57.605
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Properties and Performance of High Oleic and Palm-Based Shortenings

Abstract: Solid fat from fractionation of palm-based products was converted into cake shortening at different processing conditions. High oleic palm stearin with an oleic content of 48.2 % was obtained from fractionation of high oleic palm oil which was produced locally. Palm product was blended with different soft oils at pre-determined ratio and further fractionated to obtain the solid fractions. These fractions were then converted into cake shortenings named as high oleic, N1 and N2 blends. The physico-chemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
0
8
0
2
Order By: Relevance
“…Some research (Moon et al, 2009;Bhattacharya et al, 2006;Juttelstad, 2004;Ramli, et al, 2008) showed that trans fatty acids could raise the bad (LDL) cholesterol, lower the good blood lipids (HDL), and increased the risk of heart disease. On July 2003, the U.S. Food and Drug Administration published final rules that required trans acid content to be included on food labels by January 1, 2006(List, 2004.…”
Section: Trans Fatty Acidsmentioning
confidence: 99%
“…Some research (Moon et al, 2009;Bhattacharya et al, 2006;Juttelstad, 2004;Ramli, et al, 2008) showed that trans fatty acids could raise the bad (LDL) cholesterol, lower the good blood lipids (HDL), and increased the risk of heart disease. On July 2003, the U.S. Food and Drug Administration published final rules that required trans acid content to be included on food labels by January 1, 2006(List, 2004.…”
Section: Trans Fatty Acidsmentioning
confidence: 99%
“…High-oleic palm stearin with an oleic content of 48.2% (FA composition: C12:0, 0.2%; C14:0, 0.7%; C16:0, 26.8%; C18:0, 10.1%; C18:1c, 48.2%; C18:2c, 12.8%; C18:3, 0.3%; C20:0, 0.7%) was obtained from fractionation of high-oleic palm oil [50]. High-oleic palm oil TMP esters, with adequate PP and lubrication properties, have potential as base stocks for biodegradable lubricants [51].…”
Section: Edible Vegetable Oil Sourcesmentioning
confidence: 99%
“…I do not understand how the authors arrived at a two-layer system either. A search for articles that also describe the use of this MPOB test method revealed an article [2] by several of the same authors as the article under discussion but it described the same method verbatim. Another article [3] explains the FAME preparations as follows: ''Fatty acid methyl esters (FAME) were prepared by dissolving 50 lL oil in 950 lL nhexane with sodium methoxide (0.5 mol L -1 , 50 lL) and …''.…”
Section: Fatty Acid Compositionsmentioning
confidence: 99%
“…It is a verbatim copy of the method described in [5]. However, none of the articles [1][2][3][4][5] mentions in which solvent the sodium methoxide was dissolved; I presume that it was methanol since this compound is an essential reagent in FAME synthesis by transesterification.…”
Section: Fatty Acid Compositionsmentioning
confidence: 99%